2023
DOI: 10.1186/s13018-023-03653-4
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOTTIP impacts the proliferation and differentiation of fibroblast-like synoviocytes in ankylosing spondylitis through the microRNA-30b-3p/PGK1 axis

Abstract: Objective Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) have been reported to exert regulatory effects on biological processes. This study intended to assess the role of the lncRNA HOXA transcript at the distal tip (HOTTIP)/miR-30b-3p/phosphoglycerate kinase 1 (PGK1) axis in ankylosing spondylitis (AS). Methods Levels of HOTTIP, miR-30b-3p and PGK1 in AS synovial tissues and cultured AS fibroblast-like synoviocytes (ASFLSs) were assessed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…HOTTIP has been implicated in the pathogenesis of osteosarcoma, endochondral ossification, and osteoarthritic progression ( Kim et al, 2013 ; Li et al, 2015 ). In an experiment conducted by Wei L et al, elevated levels of HOTTIP were detected, while miR-30b-3p was reduced in AS synovial tissues and AS fibroblast-like synoviocytes (ASFLSs) in mouse models ( Wei et al, 2023 ). The study further suggested that overexpressed miR-30b-3p or inhibited HOTTIP hindered the proliferation and differentiation of ASFLSs by suppressing phosphoglycerate kinase 1(PGK1), thereby restraining AS development.…”
Section: Lncrnas Involved In the Pathogenesis Of Asmentioning
confidence: 99%
“…HOTTIP has been implicated in the pathogenesis of osteosarcoma, endochondral ossification, and osteoarthritic progression ( Kim et al, 2013 ; Li et al, 2015 ). In an experiment conducted by Wei L et al, elevated levels of HOTTIP were detected, while miR-30b-3p was reduced in AS synovial tissues and AS fibroblast-like synoviocytes (ASFLSs) in mouse models ( Wei et al, 2023 ). The study further suggested that overexpressed miR-30b-3p or inhibited HOTTIP hindered the proliferation and differentiation of ASFLSs by suppressing phosphoglycerate kinase 1(PGK1), thereby restraining AS development.…”
Section: Lncrnas Involved In the Pathogenesis Of Asmentioning
confidence: 99%
“…For example, lncRNA NKILA affects plasma TGF-β1 level [ 25 ], and lncRNA H19 mediates the release of inflammatory cytokines IL-17/IL-23 in AS [ 26 ]. Down-regulating lncRNA HOTTIP improves AS progression by inhibiting the proliferation and differentiation of fibroblast-like synovial cells [ 27 ]. Wang et al [ 28 ] have demonstrated that lncRNA HULC promotes inflammatory responses in cholangiocarcinoma by affecting the production of IL-6.…”
Section: Introductionmentioning
confidence: 99%